2016
DOI: 10.9781/ijimai.2016.3712
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Evaluation of Portfolio Approaches for Constraint Satisfaction Problems

Abstract: -In the context of Constraint Programming, a portfolio approach exploits the complementary strengths of a portfolio of different constraint solvers. The goal is to predict and run the best solver(s) of the portfolio for solving a new, unseen problem. In this work we reproduce, simulate, and evaluate the performance of different portfolio approaches on extensive benchmarks of Constraint Satisfaction Problems. Empirical results clearly show the benefits of portfolio solvers in terms of both solved instances and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…To take advantage of all cuts, the next step would be to define a portfolio solver exploiting the different kinds of cuts, the goal being to outperform each individual cut generation strategy. Portfolio approaches combine different solvers to get a globally better one, and their efficiency was already shown in the CP field [1,2,9]. [3] 115 [3] 115 [3] 115 [1] 121 118 130 [4] 130 [11] 129 [6] 130 [7] 134 134 6 133 [13] 133 [5] 133 [8] 133 [0] 154 154 150 [11] 153 [10] 153 [10] 150 [13]…”
Section: Methodsmentioning
confidence: 99%
“…To take advantage of all cuts, the next step would be to define a portfolio solver exploiting the different kinds of cuts, the goal being to outperform each individual cut generation strategy. Portfolio approaches combine different solvers to get a globally better one, and their efficiency was already shown in the CP field [1,2,9]. [3] 115 [3] 115 [3] 115 [1] 121 118 130 [4] 130 [11] 129 [6] 130 [7] 134 134 6 133 [13] 133 [5] 133 [8] 133 [0] 154 154 150 [11] 153 [10] 153 [10] 150 [13]…”
Section: Methodsmentioning
confidence: 99%
“…CPHydra, however, computes the schedule of solvers differently, and does not define any heuristic for scheduling the selected solvers. CPHydra won the 2008 International CSP Solver Competition, but subsequent investigations (Amadini et al, 2013(Amadini et al, , 2014(Amadini et al, , 2016a showed some weaknesses in scalability and runtime minimization.…”
Section: Related Workmentioning
confidence: 99%
“…Loreggia et al [47] introduce an automated way for generating an informative set of features by training a neural network on images extracted from problem instances. An evaluation of the portfolio approaches for CSPs is presented by Amadini [7,3].…”
Section: Portfolio Csp Solvers Using Machine Learningmentioning
confidence: 99%